Improvement Student Entrepreneurship Creativity through PjBL Based on Video Promotions of Jambi's Culinary Heritage in the Histoentrepreneurship Course - Merci Robbi Kurniawanti; Andre Mustofa Meihan; Mayasari (Universitas Airlangga, 2025)
In the era of the creative economy, soft skills in entrepreneurship have become one of the requirements that must be possessed by the younger generation, especially students. Students need to be trained not only to understand the theory of entrepreneurship but also to develop practical skills relevant to the local context. This study aims to improve the entrepreneurial creativity of students in the History Education study program through promotional videos based on Jambi's culinary heritage. The research method is Classroom Action Research, carried out in three cycles, each cycle consisting of planning, implementation, observation, analysis, and reflection. It was conducted in class R003 for third-semester students taking the Histo-entrepreneurship course in the 2024/2025 academic year. The results show that the application of the PjBL model with promotional videos based on Jambi's culinary heritage in the history and entrepreneurship course can improve students' entrepreneurial creativity. Students' entrepreneurial creativity increased with each cycle. In cycle I saw a percentage of 82.1%; in cycle II, 90.68%; and in cycle III, 101.2%. This study implies that students are able to develop innovative business ideas based on local wisdom and digital technology, as well as strengthen soft skills such as creativity.